Serological and molecular survey of Toxoplasma gondii infection and associated risk factors in urban cats in Kunming, Southwest China - Yang, Chunli; Liu, Songhao; Tao, Cong; Yu, Jing; Yang, Mengping; Guo, Lijuan; Bao, Liya; Li, Xiaobing; Yang, Jing; Jiang, Kangfeng (Frontiers in Veterinary Science, 2024)
Toxoplasma gondii (T. gondii) is a worldwide zoonotic parasite that can infect almost warm-blood animals, including humans, which seriously affect the health of host. Cats are known to be the only definitive host of T. gondii and continuously excrete highly infectious oocysts. This parasite carried by the companion animals leads to a great public health risk. However, there is little information on epidemiology of T. gondii in urban cats in Kunming, Southwest China.In the present study, a total of 231 serum and fecal samples were collected in Kunming aera, and then seroprevalence of T. gondii IgG antibodies in serum and molecular investigation in feces were analyzed to elucidate T. gondii infection in urban cats. The results revealed that 168 of 231 cats (72.7%) were positive for T. gondii antibodies, and 1 of 74 cat feces (1.4%) also showed a positive PCR for T. gondii DNA. The positive fecal sample was sequenced and then phylogenetically analyzed, and the isolate of T. gondii in the present study was closely related to T. gondii strain CN. In addition, the food, water and age of cats were identified as the risk factor for seropositivity. Overall, our findings indicate the widespread occurrence of T. gondii infection in pet cats in Kunming, Southwest China and identify food, water and age are the risk factors associated with T. gondii infection, which can provide effective information for developing strategies to prevent and control this zoonosis.